Experience of and Worry About Discrimination, Social Media Use, and Depression Among Asians in the United States During the COVID-19 Pandemic: Cross-sectional Survey Study - Shuya Pan; Chia-chen Yang; Jiun-Yi Tsai; Chenyu Dong (JMIR Publications, 2021)
BackgroundThe COVID-19 outbreak has spurred increasing anti-Asian racism and xenophobia in the United States, which might be detrimental to the psychological well-being of Asian people living in the United States. ObjectiveWe studied three discrimination-related variables, including (1) experience of discrimination, (2) worry about discrimination, and (3) racism-related social media use during the COVID-19 pandemic among Asians in the United States. We examined how these three variables were related to depression, and how the association between racism-related social media use and depression was moderated by personal experience of and worry about racial discrimination. MethodsA web-based, cross-sectional survey was conducted. A total of 209 people (mean age 33.69, SD 11.31 years; 96/209, 45.93% female) who identified themselves as Asian and resided in the United States were included in the study. ResultsExperience of discrimination (β=.33, P=.001) and racism-related social media use (β=.14, P=.045) were positively associated with depressive symptoms. Worry about discrimination (β=.13, P=.14) was not associated with depression. Worry about discrimination moderated the relationship between racism-related social media use and depression (β=-.25, P=.003) such that a positive relationship was observed among those who had low and medium levels of worry. ConclusionsThe present study provided preliminary evidence that experience of discrimination during the COVID-19 pandemic was a risk factor of depressive symptoms among Asian people in the United States. Meanwhile, racism-related social media use was found to be negatively associated with the well-being of US Asians, and the relationship between social media use and depression was significantly moderated by worry about discrimination. It is critical to develop accessible programs to help US Asians cope with racial discrimination both in real lives and on social media during this unprecedented health crisis, especially among those who have not been mentally prepared for such challenges.